ANALISIS BENTUK PERMASALAHAN DALAM PEMBELAJARAN IPA DI KELAS VB SDN 34/I TERATAI - lia, inayah; Eka Puspitasari, Regita; Rima Dwi Anggraini; Siti Su’adah (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to analyze the form of science learning problems for class VB SDN 34/I Teratai. The research method used in this research is a qualitative approach. The data sources in this research are the homeroom teacher of VB SDN 34/I Teratai and students of class VB SDN 34/I Teratai. Data collection techniques in this research used observation, interviews and document study techniques. The data analysis technique in this research uses the Miles and Huberman model, namely data collection, data reduction, data presentation, as well as drawing conclusions and verification. The research procedure is carried out in three stages, namely the preparation stage, the implementation stage, and the completion and report preparation stage. The results of the research show that in the VB class at SDN 34/I Teratai there are several learning problems. Through this research, it is hoped that learning can be evaluated and further improved in the future so that in learning students can understand what is being taught well.